Felt is beautiful : new possibilites for underutilized wool - Þorbjörg Valdimarsdóttir 1954- (2017)
In this thesis I talk about my roots, I have worked with natural materials and worked towards sustainable living for the past twenty years. I also research ideas from like- minded authors who want to make the environment matter and are an inspiration for a designer working in the present who wants to be responsible and work with sustainability. I talk about the Icelandic sheep, how a lot of unused wool is exported and the sellers lose sight over the production, and don ́t knows completely what happens to it. I look at the Icelandic sheep and its’ wool which is a product and a lot of it isn’t used. The opportunities that lie in the unused wool and its’ product-value are enormous. The world is big and wool is used in so many places in a various production, such as architecture, interior design and product design. I talk about a few artists using wool in various and beautiful ways, making it into something that us, Icelanders who have so much wool, have never thought about. Many of us in Iceland overlook the possibilities of wool production. I want to change that. I want to change wool into gold. Enga athugasemd